Influence of crown and hybrid abutment ceramic materials on the stress distribution of implant-supported prosthesis - João Paulo Mendes TRIBST; Amanda Maria de Oliveira DAL PIVA; Alexandre Luiz Souto BORGES; Marco Antonio BOTTINO
Abstract Introduction A new dental implant-abutment design is available with the possibility of improving aesthetic with no compromise of mechanical strength, using perforated CAD/CAM ceramic blocks. Objective This study evaluated the influence of crown and hybrid abutment ceramic materials combination on the stress distribution of external hexagon implant supported prosthesis. Method Zirconia, lithium disilicate and hybrid ceramic were evaluated, totaling 9 combinations of crown and mesostructure materials. For finite element analysis, a monolithic crown cemented over a hybrid abutment (mesostructure + titanium base) was modeled and screwed onto an external hexagon implant. Models were then exported in STEP format to analysis software, and the materials were considered isotropic, linear, elastic and homogeneous. An oblique load (30°, 300N) was applied to the central fossa bottom and the system's fixation occurred on the bone's base. Result For crown structure, flexible materials concentrate less stress than rigid ones. In analyzing the hybrid abutment, it presented higher stress values when it was made with zirconia combined with a hybrid ceramic crown. The stress distribution was similar regarding all combinations for the fixation screw and implant. Conclusion For external hexagon implant, the higher elastic modulus of the ceramic crowns associated with lower elastic modulus of the hybrid abutment shows a better stress distribution on the set, suggesting a promising mechanical behavior.